Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.apsb.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effects and mechanisms of action of a Chinese herbal medicine preparation JQ-R in vitro and in diabetic KK Ay mice

Abstract: Refined-JQ (JQ-R) is a mixture of refined extracts from Coptis chinensis (Ranunculaceae), Astragalus membranaceus (Leguminosae) and Lonicera japonica (Caprifoliaceae), the three major herbs of JinQi-JiangTang tablet, a traditional Chinese medicine (TCM) formula. The mechanisms by which JQ-R regulates glucose metabolism and improves insulin sensitivity were studied in type 2 diabetic KKAy mice and insulin-resistant L6 myotubes. To investigate the mechanisms by which JQ-R improves insulin sensitivity, a model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Although it was observed that water extract of raw RG radix could greatly increase the weight of high-fat diet (HFD) and streptozotocin (STZ)-induced diabetic mice [28]; however, the body weight of all the groups in our study increased with the experimental time and showed no significant difference among the medication groups and the model control group (Figure 1A). This result was also found in the study [29] using KK-Ay mice with the spontaneous obesity diabetic symptom. The normal control mice fed normal diet had the steady FBG levels during the experiment, ranging on average from 5.40 ± 0.76 mmol/L (at Week 0) to 7.61 ± 0.86 mmol/L (at Week 5).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Although it was observed that water extract of raw RG radix could greatly increase the weight of high-fat diet (HFD) and streptozotocin (STZ)-induced diabetic mice [28]; however, the body weight of all the groups in our study increased with the experimental time and showed no significant difference among the medication groups and the model control group (Figure 1A). This result was also found in the study [29] using KK-Ay mice with the spontaneous obesity diabetic symptom. The normal control mice fed normal diet had the steady FBG levels during the experiment, ranging on average from 5.40 ± 0.76 mmol/L (at Week 0) to 7.61 ± 0.86 mmol/L (at Week 5).…”
Section: Resultssupporting
confidence: 84%
“…The KK-Ay mice with both FBG values >7.9 mmol /L were used as diabetic models in the latter administration experiments and randomly divided into five groups containing 7 to 10 mice each. Four groups of diabetic KK-Ay mice were dosed daily by gavage with MET (200 mg/kg), RG, CC, and RG/CC (10 g/kg each) [29], respectively. Simultaneously, another fifth KK-Ay mice group (diabetic model control, abbreviated as M) and C57BL/6 J mice (normal control, abbreviated as C) were given just with the same volume of normal saline.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has a long history of use for the prevention and treatment of diabetes. Recently, much evidence-based medical data has confirmed the curative effect of TCM on diabetes and associated complications (Liu Q. et al, 2017;Gao et al, 2018;Nie et al, 2019;Xiang et al, 2019). TCM Herbal formulations are guided by the principles of compatibility and of "monarch, minister, assistant, and guide, " which are applied when deciding which combination of herbs will achieve the desired effect in treating the disease (Ma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The researches of JQJT tablets about the active ingredients [11] and quality stability [12] showed that the major biologically active fractions of JQJT tablets are from three herbal components of Coptis chinensis (the total alkaloid fraction of C. chinensis ), Astragalus membranaceus (the saponins, polysaccharides, and astragalosides of A. membranaceus ), and Lonicera japonica (the polyphenolic acid of L. japonica ). These ingredients effectively regulate blood glucose metabolism and related inflammatory responses [13]. Previous studies have indicated that these effective components (berberine, Astragalus polysaccharide and astragaloside, chlorogenic acid) have effects on the regulation of gut microbiota [1416] and protection of intestinal barrier function [1719], since gut microbiota regulation is important to improve the host low-grade inflammation and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%